2017
DOI: 10.7249/rr1893
|View full text |Cite
|
Sign up to set email alerts
|

Today's Soldier: Assessing the Needs of Soldiers and Their Families

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…As described by Trail, Sims, and Tankard (2019), and previously applied among soldiers in Sims, Trail, Chen, and Miller (2017), the TASS methodology incorporated a help-seeking and problemresolution approach to examine the most pressing challenges that Army spouses face, needs associated with those challenges, use of resources to receive help with those needs, and whether or not the needs were met by the resources used. This relatively unique and individually tailored format of the survey allows for in-depth exploration of experiences in problem resolution.…”
Section: An Overview Of Today's Army Spouse Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Trail, Sims, and Tankard (2019), and previously applied among soldiers in Sims, Trail, Chen, and Miller (2017), the TASS methodology incorporated a help-seeking and problemresolution approach to examine the most pressing challenges that Army spouses face, needs associated with those challenges, use of resources to receive help with those needs, and whether or not the needs were met by the resources used. This relatively unique and individually tailored format of the survey allows for in-depth exploration of experiences in problem resolution.…”
Section: An Overview Of Today's Army Spouse Survey Methodologymentioning
confidence: 99%
“…Furthermore, soldiers who live farther from post themselves report that they are less satisfied with the support they have received from Army resources, including support from their chain of command and other unit members, and they report less positive attitudes toward the Army and are less inclined to remain in the military (Sims, Trail, Chen, and Miller, 2017).…”
Section: The Role Of the Army Communitymentioning
confidence: 99%
“…For the domain of health and resilience, it is possible that reported differences might be associated with factors related to status and access to resources available from the military, as found in prior research (Brown et al, 2015;Meadows et al, 2018;Sims et al, 2017;Sims et al, 2018). For example, working particularly long hours on a persistent basis may negatively affect physical or mental health, and opportunities for self-care or to seek health care may be limited.…”
Section: Exploring Variation In Responses: Limited-activity Days and ...mentioning
confidence: 95%
“…Previous research has demonstrated that unmet needs can have a meaningful effect on attitudes (Sims et al, 2017). More generally, this item was considered key for the simple fact that it highlights potentially vulnerable populations-those with unresolved problems.…”
Section: Did Community Members Believe Their Greatest Needs Were Met?mentioning
confidence: 99%
See 1 more Smart Citation